PHASE BEHAVIOUR STUDY OF GAS HYDRATES: POTENTIAL OPPORTUNITIES FOR COz SEPARATION - AZMI, NURULHUDA (2012)

(untitled)
The presence of high C02 in certain natural gas reservoirs has posted huge challenges in the natural gas purification. Although there are several separation technologies like amine absorption and cryogenic process, their separation capability is limited to low C02 in natural gas. An alternative approach to separate high CO2 from C02-C& mixtures by formation of C02 hydrate is being explored in this work. The objectives were to study the phase behaviour of various gas hydrates and to investigate the effect of pressure, temperature, water and C02 compositions towards the separation of C02 from C02-C& mixtures via formation of C02 hydrates. The research work was carried out by using an established thermodynamics hydrate program, CSMGem. This work was successfully predicted the equilibrium pressures of hydrate-liquid watervapor (H-Lw-V) line for single hydrates (C&, CzH6, C3Hs, C02 and N2) with calculated AAD% less than 5%. The formation of single hydrates was found to be more favourable by increasing operating pressure and decreasing temperature. The AAD% was further improved by introducing pressure correction factor known as cavity constant, 1. It was found that the calculated AAD% for Cq2 and C3H8 hydrates were improved by 20% and 27%, respectively. The formations of binary hydrates(C&-C2Hs, C&-C3Hs, C&-C02 and C&-N2) were found to depend on the type and compositions of gases present. The equilibrium lines of mixed hydrates were located in between those of single hydrates. Introduction of cavity constant of mixture, ,Im2,, has generally improved the predicted data for all binary hydrates. The highest improvement obtained was 69% for Ch-C3Hs hydrate with C& composition of 36.2%. The separation factor on separation of COz from C02-C& mixture was found in the range of 1.0 to 2.4 in the operating conditions studied. The separation factor was increasing with decreasing of pressures, temperatures and CO2 compositions and vice-versa with water compositions. Introduction of multistage separation has further improved the separation factor from 2.3 to 22.5 for gas mixture with 30% of C02. However, it is not recommended for high C02 concentration as the number of moles in vapour phase at each stage decreases with increasing number of stages.